Demographic history, genetic connectivity, and conservation implications for the african bonytongue, Heterotis niloticus populations in West Africa - Oladimeji, Tofunmi Elizabeth (Universidade Estadual Paulista (Unesp), 2025)
The African bonytongue, Heterotis niloticus, is a commercially important freshwater fish that occurs naturally in the major rivers and basins of West Africa. In this study, we examined the demographic history of H. niloticus from inland waters in West Africa, four in Nigeria and 11 in Benin. The aim was to identify the genetic groups (populations) within these locations, assess their genetic connectivity, and infer ancestral lineages within these groups. Our findings showed that the fifteen locations sampled represent four genetic groups, as revealed by multivariate and Bayesian genetic clustering methods. These groups are Kainji Lake, Malanville, Southern Benin, and Southern Nigeria. Based on this grouping, we observed a north-to-south divergence pattern among these populations based on evolutionary model selection with Approximate Bayesian Computation (ABC). The northern groups (Kainji and Malanville) were ancestral lineages, whereas the southern groups, from Nigeria and Benin, are genetically closer with a more recent divergence. Also, we found that the population from Kainji Lake had the largest effective population size and genetic diversity estimate, while Malanville had the lowest effective population size and genetic diversity estimate. The study concluded that populations from Southern Nigeria and Southern Benin represent more connected populations, while the northern populations are genetically distinct. Evidence of bottlenecks and genetic contraction was indicated in some of the populations. These findings point to the need for management and conservation efforts that both acknowledge such demographic and genetic divergence to improve the chances of long-term use and conservation of this economically important species.

O peixe-língua-óssea africano, Heterotis niloticus, é um peixe de água doce de importância comercial que ocorre naturalmente nos principais rios e bacias hidrográficas da África Ocidental. Neste estudo, examinamos a história demográfica de H. niloticus em águas interiores da África Ocidental, quatro na Nigéria e 11 no Benim. O objetivo foi identificar os grupos genéticos (populações) nessas localidades, avaliar sua conectividade genética e inferir linhagens ancestrais dentro desses grupos. Nossos resultados mostraram que as quinze localidades amostradas representam quatro grupos genéticos, conforme revelado por métodos de agrupamento genético multivariado e Bayesiano. Esses grupos são: Lago Kainji, Malanville, Sul do Benim e Sul da Nigéria. Com base nesse agrupamento, observamos um padrão de divergência norte-sul entre essas populações, de acordo com a seleção de modelos evolutivos com Computação Bayesiana Aproximada (ABC). Os grupos do norte (Kainji e Malanville) representam as linhagens ancestrais, enquanto os grupos do sul, da Nigéria e do Benim, são geneticamente mais próximos, com uma divergência mais recente. Além disso, descobrimos que a população do Lago Kainji apresentou o maior tamanho populacional efetivo e a maior estimativa de diversidade genética, enquanto a população de Malanville apresentou o menor tamanho populacional efetivo e a menor estimativa de diversidade genética. O estudo concluiu que as populações do sul da Nigéria e do sul do Benim representam populações mais conectadas, enquanto as populações do norte são geneticamente distintas. Evidências de gargalos populacionais e contração genética foram indicadas em algumas das populações. Essas descobertas apontam para a necessidade de esforços de manejo e conservação que reconheçam essa divergência demográfica e genética, a fim de melhorar as chances de uso e conservação a longo prazo dessa espécie economicamente importante.
História demográfica, conectividade genética e implicações para a conservação das populações de Heterotis niloticus (língua óssea africano) na África Ocidental
Keywords: Tempo de divergência; Tamanho efetivo populacional; Arapaimidae; África Ocidental; Divergence time; Effective population size; Arapaimidae; West Africa